Fine-tuning the usability of a crowdsourced indoor navigation system. Issue 5 (3rd September 2019) - Ooms, Kristien; Duytschaever, Alexander; Stroeken, Koenraad; Verdoolaege, Annelies; Viaene, Pepijn; van de Weghe, Nico
ABSTRACT: This paper describes the development of a crowdsourced indoor navigation system named SoleWay. Because the input of volunteers is crucial, special attention was paid to the usability of the system at different stages throughout its development. Besides a user-friendly system, this has resulted in a number of important insights that can facilitate the development of future systems: the importance social motivation of potential users, integration of a stepwise approach (with a gradual release and subsequent user evaluations), and adaptation to user requirements. These elements combined are also crucial to be able to obtain a critical crowd that can sustain a viable content.